CHEMICAL CHARACTERIZATION OF HERBO - MINERAL SIDDHA FORMULATION KARA SOODA SATHU PARPAM BY USING MODERN TECHNIQUES - *S.D. Muralidass; R. Suganya; Hariharan S; Vasudevan R; Shree Devi M.S (International Journal of Ayurveda and Pharma Research, 2015)
Kara Sooda Sathu Parpam (KSSP) is a traditional Siddha Herbo- mineral drug. The aim of the present study was to standardize the physico-chemical traits of the Siddha herbo mineral formulation KSSP. Efforts have been made to lay down the analytical standards for Kara Sooda Sathu Parpam which were not found reported to till date. This paper appraises a detail study of physico-chemical properties, phytochemical constituents and heavy metal contents of the selected drug (KSSP) were analyzed. The total ash value was found to be 9.3 %w/w, acid insoluble ash value is 0.94%w/w, water soluble ash value is 5.5 %w/w, and loss of drying at 105 º c is  7.3 % w/w. The water soluble extractives and alcohol soluble extractives were found to be 8.67 % w/w and 5.0 % w/w. The ICP-OES reveals that the heavy metals such as Mercury, Lead, Arsenic, cadmium are present in the drug are below detected limit. HR-SEM analysis has been used to study particle size shape and distribution. The study highlights the appropriate application of modern scientific methods for developing the new insights into metal based Siddha drugs.